Carbon Aerogels Derived from Bacterial Cellulose/Polyimide Composites as Versatile Adsorbents and Supercapacitor Electrodes. Issue 3 (20th January 2016) - Lai, Feili; Miao, Yue‐E; Zuo, Lizeng; Zhang, Youfang; Liu, Tianxi
Abstract: Hierarchically structured carbon aerogels consisting of one‐dimensional carbon nanofibers and a three‐dimensional carbon skeleton are prepared by sequential imidization and carbonization of bacterial cellulose/poly(amic acid) composite aerogels. The as‐obtained carbon aerogels show excellent compressive properties, and can be directly used as versatile adsorbents for various liquids with superior sorption capacity and extraordinary recycling performance. Interestingly, the recycled carbon aerogels can still be used as electrode materials for supercapacitors with a high specific capacitance of 194.7 F g −1 and excellent stability, which is attributed to the interconnected pores for fast ion diffusion, the maximized active site exposure for efficient charge adsorptions, and crosslinked carbon nanofibers for rapid electron transport. Therefore, this work provides a new strategy to develop multidimensional carbonaceous materials for both environmental and energy applications. Abstract : Hierarchically structured carbon aerogels are prepared by sequential imidization and carbonization of bacterial cellulose (BC)/poly(amic acid) composite aerogels, and consist of 1D carbon nanofibers derived from BC and a 3D carbon skeleton derived from polyimide. These aerogels can be used both as versatile adsorbents and as supercapacitor electrodes.